Vibration control of a flexible rotor suspended by shape memory alloy wires. (July 2018) - Alves, Marco Túlio Santana; Steffen, Valder; Castro dos Santos, Marina; Savi, Marcelo Amorim; Enemark, Søren; Santos, Ilmar Ferreira
The present contribution is devoted to the study of the influence of shape memory alloys on the dynamic behavior of flexible rotors. In this sense, a suspension composed by pseudoelastic shape memory alloy wires that are connected to a rotor-bearing test rig was designed. To evaluate the performance of the system, both numerical and experimental investigations are carried out. The suspension stiffness can vary, especially in the pseudoelastic region, so that this variation takes place per a hysteretic cycle denoting energy dissipation whenever the loading magnitude is sufficient to induce a phase transformation. The constitutive model used to describe the shape memory alloy behavior is a modified version of the Brinson model for the one-dimensional case. To provide all thermomechanical properties of shape memory alloy wire, a complete characterization process was performed. Due to numerical reasons, the size of the model of the rotating system was reduced. Finally, numerical and experimental results demonstrate the success of shape memory alloy applied to the suspension of rotating machines as an interesting alternative for vibration control.